Academic Resilience of University Students Against Online Learning in the Covid-19 Pandemic - Kristina Liem; M. K. P. Abdi Keraf; Theodora Takalapeta (Universitas Nusa Cendana, 2022)
Spreading rapidly, Covid-19 cases are harming health and are also affecting various sectors, one of which is education. To reduce the number of spreads, an online learning system is being implemented. One of the educational institutions implementing this policy is the University of Nusa Cendana. This study uses a descriptive qualitative method with interview data collection methods on 5 participants. In online learning, students encounter various obstacles that create difficulties for students, so resilience is required to survive in the face of difficult circumstances. The results showed that although the students faced various obstacles and difficulties, they performed well in demonstrating their academic resilience. Students can survive difficult situations, face them and find a way out. Academic resilience enables students to do well academically and achieve positive academic performance after going through various difficulties. Academic resilience is important for students to overcome any difficulties and perform positively in academics afterward.